Evaluation of the Instruction Dignitas connubii in the Perspective of the Art of Legislation - KROCZEK, PIOTR (Prawo Kanoniczne, 2017)
In 2005 the Instruction Dignitas connubii came into force. e 10th anniversary of its binding is a good opportunity to evaluate the document in perspective of the art of legislation, that is, from the viewpoint of the principles of legislative draing and the techniques of legislative draing. The document was analyzed and some comments were made. ey refer to the very fact of establishing the instruction, and also to size, character, and type of it. e publication of the document was inspected as well. In addition, some critical comments were made about the repeating of the Code of Canon Law 1983 in Dignitas connubii. Also the hazard of the practice in question for the outcome of the process of interpretation was claried. e last remark refers to the cross references in the instruction. It can be said that the draing and establishing of the Instruction was made with disrespect and sometimes even with violation of the art of legislation.